2015
DOI: 10.1094/pdis-07-14-0708-re
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Characterization of Venturia inaequalis Reference Isolates on the Differential Set of Malus Hosts

Abstract: 23Caffier, V., Patocchi, A., Expert, P., Bellanger, Durel, M., 24 Broggini, G.A.L, Groenwold, R., and Bus V.G.M. 2014. Virulence characterization of 25 Venturia inaequalis reference isolates on the differential set of Malus hosts. Plant Dis. 26XX:XX-XX.27 28 A set of differential hosts has recently been identified for 17 apple scab resistance genes in an 29 updated system for defining gene-for-gene (GfG) relationships in the Venturia inaequalis- 30 Malus pathosystem. However, a set of reference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“… a Hybrid with hints/ab initio gene predictions for Vi1 b CEGMA analysis using both partial and full gene sequences [ 25 ] c BUSCO analysis using both partial and full gene sequences [ 26 ] d Note the recent race designation change reported for EU-B04 [ 187 ], previously reported as race (1,14) by Bus et al [ 14 ] …”
Section: Resultsmentioning
confidence: 99%
“… a Hybrid with hints/ab initio gene predictions for Vi1 b CEGMA analysis using both partial and full gene sequences [ 25 ] c BUSCO analysis using both partial and full gene sequences [ 26 ] d Note the recent race designation change reported for EU-B04 [ 187 ], previously reported as race (1,14) by Bus et al [ 14 ] …”
Section: Resultsmentioning
confidence: 99%
“…The V. inaequalis Vi1 and the V. pirina genomes ( Cooke et al, 2014 ) are publicly available via the MycoCosm genome portal at JGI 1 , 2 . All V. inaequalis and V. pirina isolates used in this study have been reported previously ( Stehmann et al, 2001 ; Le Cam et al, 2002 ; Win et al, 2003 ; Bowen et al, 2009 ; Broggini et al, 2011 ; Cooke et al, 2014 ; Caffier et al, 2015 ). The rest of the genomes were only used to extract the ALVi predicted protein sequences, these are included in the Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%
“…Further investigation of the GfG relationships at the molecular level should be performed to understand why V. inaequalis was able to overcome all five genes. Nevertheless, based on the considerable sporulation on ‘Geneva’ by, for example, EU‐NL24, a race (1,3,6,7) isolate (Caffier et al ., ), we can hypothesize that the R genes do not impose a high penalty to the pathogen for adaptation (Leach et al ., ). Nevertheless, (part of) the ‘Geneva’ R gene complex has demonstrated field resistance in New Zealand (V. Bus et al ., unpublished data), and hence will still be useful for gene pyramiding with other scab genes by breeders applying MAS enabled by our fine mapping of five ‘Geneva’ resistance loci.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of host–pathogen interactions was performed at Plant Research International in Wageningen, the Netherlands on F1 and F2 progenies derived from ‘Geneva’ using nine reference monoconidial isolates of V. inaequalis (Caffier et al ., ), including isolate 1774‐1, which was distributed as a race (3) isolate (Bus, ), but recently characterized as race (1,7) (Caffier et al ., ) (Tables and http://onlinelibrary.wiley.com/doi/10.1111/mpp.12269/suppinfo, see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%